Good Corporate Governance and Green Intellectual Capital on Tax Avoidance and Tax Audit Coverage Ratio as Moderators - Ruslim, Gunawan; Solihin, Solihin; Karsam, Karsam; Nur, Basyiruddin (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study is to analyze the extent to which GCG and GIC variables influence tax avoidance, with the tax audit coverage ratio serving as a moderating variable, in clients of Ruslim and Ruslim Public Accounting Firm. A survey method was employed to collect data from 181 respondents across 39 companies, utilizing a structured questionnaire. Data analysis was conducted using PLS SEM 3.2.8 statistical tools to assess the interaction between independent and dependent variables. The results of the study indicate that Good Corporate Governance has a significant influence on Tax Avoidance with a p-value of 0.000, and Green Intellectual Capital has a considerable influence on Tax Avoidance with a p-value of 0.000. The Tax Audit Coverage Ratio significantly influences Tax Avoidance, with a p-value of 0.000. The Tax Audit Coverage Ratio moderates the influence of Good Corporate Governance on Tax Avoidance, with a p-value of 0.004. The Tax Audit Coverage Ratio moderates the influence of Green Intellectual Capital on Tax Avoidance, with a p-value of 0.001. The implications of this study suggest that an increase in Good Corporate Governance, Green Intellectual Capital, and Tax Audit Coverage Ratio will lead to a decrease in Tax Avoidance. Tax avoidance is one of the strategies companies implement in their tax policies to minimize their tax obligations in a manner that is legally compliant with applicable tax regulations. This study also shows that companies with good GCG will engage in tax avoidance when tax audits increase, while companies with good GIC will reduce tax avoidance practices when tax audits increase. These findings are beneficial for regulators, auditors, and companies in formulating more accountable and sustainable fiscal policies.